Synthesis and evaluation of dual-action kanglemycin-fluoroquinolone hybrid antibiotics. (1st February 2022) - Peek, James; Koirala, Bimal; Brady, Sean F.
Graphical abstract: Abstract: Bacterial resistance threatens the utility of currently available antibiotics. Rifampicin, a cornerstone in the treatment of persistent Gram-positive infections, is prone to the development of resistance resulting from single point mutations in the antibiotic's target, RNA polymerase. One strategy to circumvent resistance is the use of 'hybrid' antibiotics consisting of two covalently linked antibiotic entities. These compounds generally have two distinct cellular targets, reducing the probability of resistance development and potentially providing simplified pharmacological properties compared to combination therapies using the individual antibiotics. Here we evaluate a series of semi-synthetic hybrid antibiotics formed by linking kanglemycin A (Kang A), a rifampicin analog, and a collection of fluoroquinolones. Kang A is a natural product antibiotic which contains a novel dimethyl succinic acid moiety that offers a new attachment point for the synthesis of hybrid antibiotics. We compare the activity of the Kang A hybrids generated via the acid attachment point to a series of hybrids linked at the compound's naphthoquinone ring system. Several hybrids exhibit activity against bacteria resistant to Kang A via the action of the partnered antibiotic, suggesting that the Kang scaffold may provide new avenues for generating antibiotics effective against drug-resistant infections.